Investigation Of Responsibility Attitude and Increasing Student Awareness Through the MAS ECO Program at SDN 43 Mataram - Nirmala, Arisandi; Weddayu Murferatiwi, Baiq; Merpati Dirgantari, Virgynia; Khairina, Dita; Bayan, Lalu; Herianto, Edy; Sumardi, Lalu (International Journal of Social Science, Education, Communication and Economics, 2024)
This research aims to describe the management of plastic and organic waste through the MAS ECO program (zero waste food with ecobricks) through lunch boxes and the ECO (ecobrick) method which can instill an attitude of responsibility and increase the awareness of students at SD Negeri 43 Mataram. This research uses desciptive qualitative approach. The subjects in this research were Class V students of SDN 43 Mataram. The object of this research is to build students' character of responsibility and awareness of the environment. This research was carried out at SDN 43 Mataram in the even semester of the 2023/2024 academic year. Data collection techniques use observation, interview, and documentation techniques. The data analysis used in this research is data analysis from Milles and Huberman which consists of data reduction, data presentation, drawing conclusions/verification. The research results show that the MAS ECO Program at SDN 43 Mataram has succeeded in increasing students' responsibility and awareness of the environment. This is proven by the students' activeness in reducing waste through lunch boxes and managing ready-to-tube plastic waste in ecobrick bottles every day. Students' awareness of the environment is getting better by keeping the school environment clean every day.